HUBUNGAN SELF-EFFICACY DENGAN KADAR GLUKOSA DARAH PASIEN DIABETES MELITUS TIPE II - Heltty Heltty; Nazaruddin Nazaruddin (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2023)
Diabetes mellitus (DM) is a metabolic disorder characterized by the body's inability to use glucose, fat and protein due to insulin deficiency or insulin resistance which results in an increase in blood glucose levels. Type II DM is estimated to rank seventh in the cause of death in the world in 2030. Indonesia is the only country in Southeast Asia that contributes the most to the prevalence of diabetes cases in Southeast Asia. Control of high blood sugar levels needs to be done. DM sufferers need to grow confidence in themselves that they are able to control their blood sugar levels independently. The purpose of this study was to determine the relationship between self-efficacy and blood glucose levels in Type II diabetes mellitus patients. This type of research was a quantitative study using a cross sectional study design, with a sample of 75 respondents. Based on the statistical test results, the results obtained were X2 count > X2 table and the Fisher's Exact Test value was 0.000 < ɑ 0.05. There was a relationship between self-efficacy and blood glucose levels in type II DM patients and based on test results the phi coefficient (φ) is obtained (φ) = 1,000 which means that it indicates a strong relationship between self-efficacy and blood glucose levels in type II diabetes mellitus patients. Growing confidence in individuals needed to carry out independent care at home